NILAI-NILAI RELIGIUS NOVEL “PULANG” KARYA TERE LIYE - Wulan Handayani; Ilyas Ichsani (Al Aqidah (Jurnal Studi Islam), 2019)
There are two elements contained in the works of Tere Liye that is pleasure and wisdom. A good novel is one that can move the heart, mind, and feelings of the readers to the awareness leading to good deeds, avoiding wrong and deviant actions, reminds them of something missing and out of their attention, as a soul empowerment and a wakeup call to understanding. Accentuated with aesthetic delivery of unique and impressive diction, the religious values are inserted and bound by Tere Liye to the dialogues and monologues in his work explicitly and implicitly creating a worth-reading novel to be explored, understood, and enjoyed by the young generation who are in charge of running the wheel of life on this earth in the future with full submission to Allah the Almighty while having an excellent self-control and intellectually, emotionally, and spiritually brilliant.